Shattered nation: inequality and the geography of a failing state - Dorling, D (Verso Books, 2023)
Britain is broken, but how did it become so divided? Britain was once the leading economy in Europe; it is now the most unequal. In Shattered Nation, leading geographer and author of Inequality and the 1% shows that we are growing further and further apart. Visiting sites across the British Isles and exploring the social fissures that have emerged, Danny Dorling exposes a new geography of inequality. Middle England has been hit hard by the cost-of-living crisis, and even people doing comparatively well are struggling to stay afloat. Once affluent suburbs are now unproductive places where opportunity has been replaced by food banks. Before COVID, life expectancy had dropped as a result of poverty for the first time since the 1930s. Fifty years ago the UK led the world in child health; today, twenty-two of the twenty-seven EU countries have better mortality rates for newborns. No other European country has such miserly unemployment benefits; university fees so high; housing so unaffordable; or a government economically so far to the right. In the spirit of the 1942 Beveridge Report, Dorling identifies the five giants of twenty-first-century poverty that need to be conquered: Hunger, Precarity, Waste, Exploitation, and Fear. He offers powerful insights into how we got here and what we must do in order to save Britain from becoming a failed state.